Nanomaterial Endocytosis: Quantification of Adsorption and Ingestion Mechanisms - Abhinav Sannidhi; Chen Zhou; Young Suk Choi; Allan E. David; Paul W. Todd; Thomas R. Hanley (Magnetochemistry, 2023)
The widespread use of nanomaterials in vaccines, therapeutics, and industrial applications creates an increasing demand for understanding their ingestion by living cells. Researchers in the field have called for a more robust understanding of physical/chemical particle–cell interactions and a means to determine the particles ingested per cell. Using superparamagnetic nanobeads, we measured the beads per cell and quantified the kinetics of the receptor-independent endocytosis of particles having seven surface chemistries. Poly(ethylene glycol) (PEG)-coated nanoparticles were ingested less effectively by cultured Chinese hamster ovary (CHO-K1) cells and more effectively by aminated nanoparticles than starch-coated particles. The cells ingested 2 to 4 × 105 of the most attractive particles. The interplay between Van der Waals and coulombic potentials was quantified on the basis of Derjaguin–Landau–Verwey–Overbeek (DLVO) theory modified to include hydration repulsion using physical parameters of the seven surface chemistries. Using dose–response curves for inhibitors of clathrin- or caveolae-dependent ingestion, we quantified how particle surface chemistry determines which endocytic pathway is used by the cell. Such characterization can be useful in predicting nanomaterial uptake in medical and toxicological applications and in the selection of particle surface chemistries for receptor-dependent endocytosis.